2022
DOI: 10.3389/fgene.2022.927046
|View full text |Cite
|
Sign up to set email alerts
|

A Pan-Cancer Analysis Reveals the Prognostic and Immunotherapeutic Value of Stanniocalcin-2 (STC2)

Abstract: Background: Stanniocalcin-2 (STC2) is a secreted glycoprotein which plays an important role in regulating the homeostasis of calcium, glucose homeostasis, and phosphorus metastasis. Accumulating evidence suggests that STC2 is implicated in cancer mechanisms. However, the effects of STC2 on cancer development and progression across pan-cancer are not yet completely known.Methods: Data were downloaded from The Cancer Genome Atlas database to obtain differentially expressed genes significantly associated with pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…also reported that STC2 promoted pancreatic cancer migration, invasion, and EMT ( 79 ). A pan-cancer research found that STC2 was closely related to tumor immune microenvironment including immune cell infiltration, ICGs, MMRs, TMB, and MSI ( 80 ). One bioinformatic analysis reported that overexpression of CCT6A in tumor tissue was associated with poor breast cancer prognosis ( 81 ).…”
Section: Discussionmentioning
confidence: 99%
“…also reported that STC2 promoted pancreatic cancer migration, invasion, and EMT ( 79 ). A pan-cancer research found that STC2 was closely related to tumor immune microenvironment including immune cell infiltration, ICGs, MMRs, TMB, and MSI ( 80 ). One bioinformatic analysis reported that overexpression of CCT6A in tumor tissue was associated with poor breast cancer prognosis ( 81 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, pan‐cancer analysis has revealed that some cancers arising from different organs exhibit molecular similarities, while certain cancers originating from the same tissue can have distinct genomic profiles 11,12 . Numerous studies have been conducted to explore the expression level of one specific gene in various cancers 13–15 . Recently, the prognostic significance, and immunological functions of ubiquitin‐conjugating enzyme 2C (UBE2C) has been studied across various tumor types 16,17 …”
Section: Introductionmentioning
confidence: 99%
“…11,12 Numerous studies have been conducted to explore the expression level of one specific gene in various cancers. [13][14][15] Recently, the prognostic significance, and immunological functions of ubiquitin-conjugating enzyme 2C (UBE2C) has been studied across various tumor types. 16,17 In the current study, we aimed to detect differentially expressed gene among various cancer types.…”
mentioning
confidence: 99%
“…Numerous studies have been conducted to explore the expression level of one speci c gene in various cancers and its correlation with diagnosis, prognostic signi cance, and immunological functions (18,19,20). These ndings suggested that identifying deregulated genes and molecular aberrations in several tumor types is essential for extending cancer therapies effective in one cancer type which can be applied to others with a similar genetic pro le.…”
Section: Introductionmentioning
confidence: 99%